Green Economy milestones and opportunities - Mukherjee, A; Pramanik, P; Chakrabarti, B; Maity, A; Sharma, D K (Indian Farming, 2017)
Humans as global citizens have to think in a rational and emotional way. From being an individual single citizen to international level is required to maintain aesthetic beauty of nature and habitability of our earth. And that’s why European Environment Agency suggests greening the economy in a simple way. Increasing some tax rates and removing subsidies on environmentally harmful products and services can boost economic growth if the revenue generated is then used to relieve the tax burden on employment and investment.